Intubation-Related Laryngeal Deficiency and Vocal Fold Immobility in Pediatric Premature Patients - Zur, Karen B; Douglas, Jennifer; Carroll, Linda M (The Laryngoscope, 2021)
We report a posterior laryngeal rating system and measures of voice disability in pediatric patients undergoing phonosurgery for vocal fold paralysis. Posterior glottic deficiency may account for persistent voice disability. Retrospective Study. Retrospective analyses of 66 subjects with primary unilateral vocal fold paralysis were reviewed for the status of posterior glottis and voice disability (Pediatric Voice Handicap Index [pVHI]). Gestation age (GA), weight, and medical/surgical history were reviewed. The width, length, and depth of the larynx were analyzed to create a reproducible rating scale. Mean GA was 29 weeks, with an intubation history for all subjects, with 90% having a left vocal fold immobility. Cardiac surgery was performed in 92% of subjects. A progressive rating (type 0-3) Benjamin Defect Severity Scale (BDSS) was developed to rate the absence or presence of a posterior abnormality. BDSS-2 and BDSS-3 subjects were more likely to have low birth weight. Extremely preterm GA was more likely to be associated with BDSS-1 (mild) or BDSS-2. History of multiple and prolonged intubations were seen more frequently in BDSS-2 or BDSS-3. Post-op pVHI reduced an average of 15 points for BDSS-0 to BDSS-2, but only 3 points for BDSS-3. Post-op pVHI matched normal values for preintervention dysphonic children. The presence of a persistent breathy voice after intervention for unilateral vocal fold immobility is potentially associated with posterior glottic defects. Low birth weight with multiple/prolonged intubation is more likely to be present with higher-grade BDs, whereas low GA is more likely to be associated with BDSS-1 to BDSS-2. 4 Laryngoscope, 2021.